Romanian-American Negotiations in Education, Science, Culture, and Arts - MIHALY, Roxana; ANDRAȘ, Sonia D.; SIGMIREAN, Cornel (Presa Universitară Clujeană, 2023)
As a political model for the young democracy in interwar Romania, as a protector against threats to the sovereignty and integrity of the state, as a cultural model, and as a daily life, America represented for Romania a reference point, a factor of stability and progress. America was a model and ally of the civilized world! Unfortunately, isolated in the interwar period from the political realities on the continent, America saw how, at the end of the ‘30s, the political creation of the Paris Peace Conference collapsed, the US being invited to “abandon jazz” to enter a new war on the European continent, extended to Asia and Africa, to save civilization, alongside the UK. At the war’s end, Eastern Europe fell victim to communist totalitarianism imposed by the USSR, and its peoples were forced to abandon the Western model of civilization in favor of the communist model. However, after 45 years of communism, the American model became negotiable again as a cultural, economic, and political model for Romanians, allowing us to reconstruct essential pages in the history of interwar Romania in the context of Romanian- American relations.